Knowledge co-production for identifying indicators and prioritising solutions for food and land system sustainability in Australia - Romy L. Zyngier; Carla L. Archibald; Brett A. Bryan; Haley Lambert; Enayat A. Moallemi; Mark Elliott; Mark Lawrence; Jane Hutchinson; Lauren T. Bennett; Timothy Reeves; Matthew Pryor; Ulrika Lindholm; et al. (Sustainability Science, 2024)
Achieving sustainable Australian food and land systems requires the rapid implementation and scaling up of a broad suite of solutions to meet the Sustainable Development Goals (SDGs). Decision-making frameworks are needed to identify suitable indicators and prioritise solutions at national scales to inform sustainability transitions. Using a knowledge co-production framework, we convened 150 stakeholders from 100 + organisations to identify 18 nationally relevant indicators that aligned with critical SDGs describing a sustainable food and land system for Australia, in addition to 78 key solutions (supply- and demand-side) to enable progress against these indicators. We then asked subject matter experts to code the impact of each solution on each indicator using an adapted interaction mapping method accounting for uncertainty. The solution category ‘Protecting and restoring nature’, which included solutions targeting conservation and restoration, showed the highest potential for capturing synergies and avoiding trade-offs across multiple indicators. This category exhibited 34.6% of total major synergies, supporting the achievement of clean water and sanitation (SDG6), economic growth (SDG12), life under water (SDG14), and life on land (SDG15). The solution category ‘Carbon sequestration’, which included technological and biological carbon dioxide removal solutions, had the highest number of trade-offs with individual sustainability indicators (42.3%), particularly those relating to zero hunger (SDG2), wellbeing (SDG3), SDG6, SDG14, and SDG15. Our framework can be used to inform future research investment, support the prioritisation of solutions for quantitative modelling, and inform discussions with stakeholders and policymakers for transforming national-scale food and land systems in alignment with the SDGs.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Characterization of heterogeneous skin constructs for full thickness skin regeneration in murine wound models - Marytheresa Ifediba; Nicholas Baetz; Lyssa Lambert; Haley Benzon; Vonda Page; Nicole Anderson; Stephanie Roth; James Miess; Ian Nicolosi; Sarah Beck; Nikolai Sopko; Caroline Garrett (Tissue and Cell, 2024)